Plasma desmosine for prediction of outcomes after acute myocardial infarction - Ali, Kashan; Israr, Muhammad Zubair; Ng, Leong L.; Mordi, Ify; Lang, Chim C.; Kuzmanova, Elena; Huang, Jeffrey T-J; Choy, Anna-Maria (Frontiers in Cardiovascular Medicine, 2022)
Background: Elastin degradation is implicated in the pathology of vulnerable plaque. Recent studies show promising results for plasma desmosine (pDES), an elastin‐specific degradation product, as a marker of cardiovascular disease (CVD) outcomes. The aim of this study was to investigate the potential role of pDES as a marker of clinical outcome in patients with acute myocardial infarction (AMI). Methods: In this case-control study, we studied 236 AMI patients: 79 patients who had death and/or MI at 2 years, and 157 patients who did not have an event at 2 years. pDES was measured using a validated liquid chromatography-tandem mass spectrometry method. Association of pDES with adverse outcomes, and the incremental value of pDES to GRACE score for risk stratification was assessed. Results: pDES levels were elevated in patients with the composite outcome of death/MI at 2 years (p=0.002). Logistic regression analyses showed pDES to be associated with death/MI at 2 years [Odds ratio 5.99 (95%CI 1.81-19.86) p=0.003]. pDES remained a significant predictor of death/MI at 2years even after adjustment for age, sex, history of CVD, revascularisation, blood pressure, medications on discharge, Troponin I, and NT-proBNP levels.[OR 5.60 (95%CI 1.04-30.04) p=0.044]. In another multivariable model including adjustment for eGFR, pDES was significantly associated with the composite outcome at 6months, but not at 2years follow up. DES was also able to reclassify risk stratification for death/MI at 6 months, when added to the GRACE risk model [Net Reclassification Index 41.2 (95% CI 12.0-70.4) p=0.006]. Conclusions: pDES concentrations predict clinical outcomes in patients with AMI, demonstrating its potential role as a prognostic marker in AMI.